2020
DOI: 10.5114/aoms.2019.83511
|View full text |Cite
|
Sign up to set email alerts
|

Association of circulating cystatin C levels with type 2 diabetes mellitus: a systematic review and meta-analysis

Abstract: A b s t r a c tIntroduction: This study aimed to systemically summarize the present literature about circulating cystatin C (Cys C) levels in type 2 diabetes mellitus (T2DM) and provide a more precise evaluation of Cys C levels in T2DM. Material and methods: Relevant studies about Cys C concentrations in T2DM were searched in PubMed, EMBASE and the Cochrane Library database (up to Oct 31 2018). We computed the pooled standard mean difference (SMD) with its 95% confidence interval (CI) of Cys C levels through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
2
13
0
1
Order By: Relevance
“…The same SNP also shows maternal effects on HDL cholesterol and apolipoprotein A, both tightly related to T2D [25][26][27][28] . At 11p15.5, we found rs2237892, rs231362 and rs2334499 associated through different types of PofO effects with Cystatin C, another putative biomarker for T2D [29][30][31] . Finally, the T allele of rs2334499 seems to decrease multiple weight-and fat-related phenotypes when paternally inherited, and conversely increase them when maternally inherited.…”
Section: Replication Of Known Pofo Associationsmentioning
confidence: 80%
“…The same SNP also shows maternal effects on HDL cholesterol and apolipoprotein A, both tightly related to T2D [25][26][27][28] . At 11p15.5, we found rs2237892, rs231362 and rs2334499 associated through different types of PofO effects with Cystatin C, another putative biomarker for T2D [29][30][31] . Finally, the T allele of rs2334499 seems to decrease multiple weight-and fat-related phenotypes when paternally inherited, and conversely increase them when maternally inherited.…”
Section: Replication Of Known Pofo Associationsmentioning
confidence: 80%
“…The effects of the active forms of GLP-1 are mediated by a G protein-coupled receptor, GLP-1R, which is expressed in several sites, including enteric and vagal nerves, the stomach, pancreas, intestine, and various regions of the brain [29]. The physiological functions of GLP-1 include insulin secretion stimulation; glucagon secretion inhibition; protecting β-cells through endoplasmic reticulum stress reduction; reduction of food intake; stomach emptying reduction, thereby reducing the postprandial glucose peak; improvements in cardiomyocyte glucose utilisation, cardiac function, and cardiovascular protection [25,30,31]; and appetite suppression at the level of the hypothalamus and the promotion of weight loss [32][33][34]. Additionally, recent evidence suggests that GLP-1 RA may have a direct action (independent of central nervous system (CNS) actions) in the white adipose tissue inducing browning, enhancing lipolytic capacity and mitochondrial biogenesis [35].…”
Section: Discussionmentioning
confidence: 99%
“…In Shankar and Teppala this association has been found for women, but not for men in a cross-sectional study design 12 . A systematic review and meta-analysis by Ma et al demonstrated that type 2 diabetes mellitus patients had higher cystatin C compared to healthy controls 13 . In a meta-analysis by van der Laan et al cystatin C was associated with several cardiovascular risk factors and traits like LDL, HDL, BMI, diastolic blood pressure and smoking.…”
Section: Introductionmentioning
confidence: 99%